Dyspnea Experience and Dyspnea Management in Patients with Chronic Obstructive Pulmonary Disease in Bangladesh - Parveen, Shahanaz; Thaniwattananon, Ploenpit; Matchim, Yaowarat (Nurse Media Journal of Nursing, 2014)
Purpose: This study aimed to evaluate dyspnea experience and dyspnea management intervention used by Chronic Obstructive Pulmonary Disease (COPD) patients in Bangladesh.Methods: A descriptive cross-sectional design was used. The symptom management model developed by Dodd et al. was used to guide the study. Data were collected from 140 COPD patients by using self-report questionnaire. Descriptive statistics was used to analyze the data.Results: The patients perceived dyspnea difficulty within the past 24 hours and within the past 7 days at moderate level. The most used dyspnea management methods included bronchodilators, leaning forward position, and keeping still. The patients perceived bronchodilators as somewhat effective method and perceived leaning forward position as quite a bit effective method in reducing dyspnea.Conclusion: The study could guide nurses to promote dyspnea management intervention for COPD patients in Bangladesh, in order to enhance higher quality of life.